Vulnerabilidade ambiental da zona costeira de Pititinga, Rio do Fogo, Rio Grande do Norte - Lima, Eduardo Queiroz de (2010)
This work presents a study on the environmental vulnerability of the coastal region of Pititinga, Rio do Fogo/RN. The coastal erosion of Pititinga beach was analyzed and considerated as one more process that produces environmental vulnerability in the area of study, taking into account its human and natural environment and establishing the relation between them, to understand the arrangement that produced its spatial configuration. The natural environment was expressed by thematics maps with geology, geomorphology, vegetation and soil themes, while the human environment was expressed by the use and occupation of the soil map. The coastal erosion was put in an erosion vulnerability map. The methodological procedure to generate the thematics maps, vulnerability maps and of the erosion coastal involved the bibliographic research, field visits with check-list form fill, collect and analysis of sediment sample, photo-interpretation techniques, integration of the information in a database, data store and spatial analysis in a Geographic Information System (GIS) ambient. The natural vulnerability map shows a predominancy of environments with low (29,6%) or medium (42,4%) vulnerability, pointed the frontal and mobile dune as the areas with the highest vulnerability. The environmental vulnerability map, presents a predominancy of environments with low vulnerability (53,8%), with the high vulnerability concentrated on Pititinga community. The coastal erosion vulnerability presented distinct behaviors on three sections among the coastal line according each one characteristics. Where there are frontal and transgressive dunes, vulnerability are, generally, medium or low, respectively, and in the absence of them, as what occurs in Pititinga community, the vulnerability is predominately very high